2021
DOI: 10.3762/bjoc.17.36
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected rearrangements and a novel synthesis of 1,1-dichloro-1-alkenones from 1,1,1-trifluoroalkanones with aluminium trichloride

Abstract: A novel reactivity of 1,1,1-trifluoroalkanones is reported, where the reaction with AlCl3 results in the formation of 1,1-dichloro-1-alkenones. The reaction scope was found to be broad, with various chain lengths and aryl substituents tolerated. For substrates containing an electron-rich aromatic ring, further reactions take place, resulting in bicyclic and/or rearrangement products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Also, the isomer with the highest electrophilicity index is (5,8a) chromen. The highest E HOMO , softest, is acquired by (6,8)-chromen and hence it has the lowest ionization potential, lowest value for hardness, and lowest electrophilicity index. The HOMOs, LUMOs, and related properties mentioned above, calculated according to the (GO + DC) procedure, are in complete numerical agreement with the same properties calculated using the (GO/SPDC) procedure as in Part I of this investigation.…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the isomer with the highest electrophilicity index is (5,8a) chromen. The highest E HOMO , softest, is acquired by (6,8)-chromen and hence it has the lowest ionization potential, lowest value for hardness, and lowest electrophilicity index. The HOMOs, LUMOs, and related properties mentioned above, calculated according to the (GO + DC) procedure, are in complete numerical agreement with the same properties calculated using the (GO/SPDC) procedure as in Part I of this investigation.…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 99%
“…Structure (III) of Figure 6 is responsible for the ICT that occurs in the (5,7)-dichloro amino chromen due to the push−pull interaction between the amine group and the π-bond system of the dichlorophenyl ring. The other chromen isomers (5,8), (5,6), (6,7), and (6,8) possess at least one resonance structure that accommodates a negative charge due to resonance on the carbon bonded to the chlorine, as shown in Figure 7. Resonance structures of (5,6), (5,8), (6,8), (6,7), and (5,8a)chromen isomers.…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, g-trifluoromethylated ketones and trifluoromethylated sulfonyl ketones are important building blocks (Figure 1C). [41][42][43][44][45][46][47] Nonetheless, methods for the synthesis of both types of compounds have been seldomly reported. Herein, a base-controlled reincorporation/release of SO 2 within a photocatalyzed radical difunctionalization of alkenes is described, offering a switchable gateway toward a series of otherwise difficult-to-obtain g-trifluoromethylated ketones and trifluoromethylated sulfonyl ketones (Figure 1B).…”
Section: The Bigger Picturementioning
confidence: 99%
“…McLeod observed the halodefluorination and dehydrochlorination of 1,1,1-trifluoroalkanones using superstoichiometric aluminum chloride (Scheme 23). 36 Trifluoroalkyl substrates not supported by a conjugated electronic system have much higher barriers toward C-F activation as compared to the gem-difluoroalkane systems utilized by Shibata (see above), 35 and it was found that the presence of the ketone group was essential for generation of the desired product. The reaction was hindered in the presence of strong donors, such as pyridines, and the alkyl chain length between the trifluoromethyl group and the carbonyl group affected the product yield greatly.…”
Section: Cascade Reactions Involving Halodefluorinationmentioning
confidence: 99%